1994
DOI: 10.1021/jm00045a025
|View full text |Cite
|
Sign up to set email alerts
|

Tricyclic Analogs of Acyclovir and Ganciclovir. Influence of Substituents in the Heterocyclic Moiety on the Antiviral Activity

Abstract: The effect of substitution in the tricyclic moiety of 3,9-dihydro-9-oxo-5H-imidazo[1,2-alpha]purine (1,N-2-ethenoguanine) analogues of acyclovir (1) and ganciclovir (2) on their physical properties and antiherpetic activity was investigated by synthesizing a series of compounds substituted in the 2, 6, or 7 position (6-14). Substitution in the 6-position with phenyl or 4-biphenylyl resulted in fluorescent compounds (7, 9, 13, 14). In general, the substituent in the 6 position potentiated the antiviral activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
0

Year Published

1995
1995
2010
2010

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 6 publications
0
27
0
Order By: Relevance
“…2,3 In the case of the reaction of 1 and 2 with 2-bromopropiophenone, we isolated, in addition to the expected 6-Ph-7-Me-TACV 17 and 6-Ph-7-Me-TGCV 28, the intermediate N-1 alkylation products: 1-(1-benzoylethyl)-ACV 17′ and 1-(1-benzoylethyl)-GCV 28′. The structures of 17′ and 28′ were identified on the basis of their HR MS and 1 H and 13 C NMR spectra.…”
Section: Chemistrymentioning
confidence: 99%
See 3 more Smart Citations
“…2,3 In the case of the reaction of 1 and 2 with 2-bromopropiophenone, we isolated, in addition to the expected 6-Ph-7-Me-TACV 17 and 6-Ph-7-Me-TGCV 28, the intermediate N-1 alkylation products: 1-(1-benzoylethyl)-ACV 17′ and 1-(1-benzoylethyl)-GCV 28′. The structures of 17′ and 28′ were identified on the basis of their HR MS and 1 H and 13 C NMR spectra.…”
Section: Chemistrymentioning
confidence: 99%
“…We have previously reported that linking the 2-NH 2 and N-1 positions of guanine moiety of acyclovir (ACV, 1) and ganciclovir (GCV, 2) with an etheno bridge to form derivatives of the tricyclic 3,9-dihydro-9-oxo-5H-imidazo[1,2-a]purine system, TACV (3) and TGCV (4) [For the systematic names 3,9-dihydro-3-[(2-hydroxyethoxy)methyl]-9-oxo-5H-imidazo[1,2-a]purine and 3,9-dihydro-3-[(1,3-dihydroxy-2-propoxy]-9-oxo-5H-imidazo-[1,2-a]purine the abbreviations TACV and TGCV, respectively, are used throughout this paper. ], allows for the modulation of physical and biological properties of the parent antivirals.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…± When we treated 6-aryl substituted compounds 6-Ph-TACV (1a) [6] or 6-(4-MeOPh)-TACV (1b) [7] in DMF with solid K 2 CO 3 followed by Ph 3 CCl, we found products that carried C(7)-substituents being either 4-(benzhydryl)phenyl (2a and 2b), or substituted 4-(benzydryl)phenyl (3a, 3b, and 4a) (Scheme). Their structures were assigned on the basis of 1 H-and 13 C-NMR, and mass spectra.…”
mentioning
confidence: 99%